Implementing Hidden Chart Media to Enhance Elementary Students’ Learning Outcome in Science - Gustimal Witri; Fitri Islami; Mahmud Alpusari; Afrianto Afrianto (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2018)
The study aims to enhance students’ learning outcome in science class by implement cooperative learning model with hidden chart media. Method of study is a classroom action research. The subject is a fifth grade, consisting of 25 students; 14 boys and 11 girls. The research instruments are test sheets, teacher and student observation sheets, and documentation files. The results show an improvement over each cycle. Teacher activity in first cycle was 70.83%, and increased to 79.17%. In second cycle was 91.67%, and increased to 95.83. Student activity in first cycle was 62.50%, and enhance to 75%. In cycle II was 83.33%, and enhance to 87.50%. The student's average score also shows improvement. The base rate is 59.60; increased to 70.72 at UH I, and increased to 79.04 in UH II. Based on these results, it can be concluded that the implementation cooperative learning model with hidden chart media can enhanceprimary students’ learning outcomes in science.